2020
DOI: 10.1073/pnas.1920621117
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis epigenetic regulator ICU11 as an accessory protein of Polycomb Repressive Complex 2

Abstract: Molecular mechanisms enabling the switching and maintenance of epigenetic states are not fully understood. Distinct histone modifications are often associated with ON/OFF epigenetic states, but how these states are stably maintained through DNA replication, yet in certain situations switch from one to another remains unclear. Here, we address this problem through identification ofArabidopsisINCURVATA11 (ICU11) as a Polycomb Repressive Complex 2 accessory protein. ICU11 robustly immunoprecipitated in vivo with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
40
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 38 publications
5
40
1
Order By: Relevance
“…In addition, our results indicate that chromatin accessibility can be further reduced by EMF1. This plant-specific protein has been shown to associate with PRC2 and to be required for H3K27me3 marking 19,[21][22][23][24][25] . Accordingly, loss of EMF1 function affected H3K27me3 levels but not H2AK121ub.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, our results indicate that chromatin accessibility can be further reduced by EMF1. This plant-specific protein has been shown to associate with PRC2 and to be required for H3K27me3 marking 19,[21][22][23][24][25] . Accordingly, loss of EMF1 function affected H3K27me3 levels but not H2AK121ub.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent data showed that EMF1 co-purifies with PRC2 (refs. [21][22][23] ) and is required for H3K27me3 marking 19,24,25 . Likewise, LHP1 was proposed to perform similar function to Drosophila PRC1 component Polycomb (Pc) 26,27 ; however, LHP1 also co-purifies with PRC2 (refs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…EOL1 physically interacts with LHP1 and CLF, and together they mediate the deposition of H3K27me3, suggesting that EOL1 assists with the activities of PRC1 and PRC2 [ 98 ]. INCURVATA11 ( ICU11 ), encoding a 2-oxoglutarate-dependent dioxygenase, has been reported to have histone demethylation activity in other organisms [ 99 , 100 ]. In Arabidopsis , the icu11 mutant resembles clf leaves by having upward curly leaves.…”
Section: Post-embryonic Developmental Transitions Mediated By Prc2 and Prc1mentioning
confidence: 99%
“…Mutations in icu11 and its close paralog cupuliformis2 ( cp2 )result in flowering without any vegetative growth, mimicking emf1 or emf2 mutants [ 100 ]. ICU11 robustly interacts with PRC2 core components and binds to the nucleation region of FLC to mediate the demethylation of H3K36me3 (an active marker at FLC ) ( Figure 4 b), suggesting that it controls the switch between H3K36me3 and H3K27me3 at FLC [ 99 ]. Together, ALP1, EOL1, ICU11, and CP2 are accessory proteins of PRC2.…”
Section: Post-embryonic Developmental Transitions Mediated By Prc2 and Prc1mentioning
confidence: 99%